Otimização da síntese de 1,2,4,5-tetraoxanos assimétricos visando à obtenção de derivados do ácido -naftalenoacético - Isabel Alejandra Valero Antolinez (2015)
1,2,4,5 - tetraoxanes are compounds characterized by the presence of peroxidic bonds within its structure. The synthesis of these compounds has been widely studied because of its great antimalarial potential. Recently, our research group discovered that these compounds also exhibit phytotoxic activity with excellent results in the growth inhibition of weeds in equal proportions to commercial herbicides. However, reaction yields during the preparation process are extremely low. The formation of these compounds occurs in an equilibrium reaction, which leads to formation of several byproducts. Thus, the first part of this study aimed to optimize the reaction conditions of the two steps involving the synthesis of tetraoxanes. The 3 -phenyl- 1,2,4,5 tetraoxospiro [5.5 ] undecane was the compound chosen for the optimization methodology. The first stage of teraoxane synthesis is to obtain gem-dihydroperoxides from carbonyl compounds and hydrogen peroxide. The gem-dhyidroperoxide was obtained from benzaldehyde, and the parameters studied during the optimization process in this step were, catalyst, concentration of hydrogen peroxide, polarity of the medium and temperature. The tin chloride II showed to be the most suitable catalyst for this reaction, providing the product in 50 % yield. By analyzing the hydrogen peroxide concentration, we fiund that a higher concentration favors the formation of product. The experiments carried out to study the effect of temperature, revealed that its increase prevents the formation of the product. The second phase of the study consisted in forming the tetraoxane from a dihydroperóxide condensation with a carbonyl compound. In this step were studied the effect of different catalysts, their amount and type of solvent. Of all tested catalysts, sulfuric acid at 50 mol % was the best producing the product in 46% yield. Regarding the use of the solvent, dichloromethane was the best reaction medium. The second part of the study aimed to enter the tetraoxanic ring in the structure of a commercial herbicide, such, - naphtalenacetic acid, in order to increase their activity and the time for action. For this, the acid function of the compound was reduced to the aldehyde and then condensed with 1,1-dihydroperoxiciclohexane. The product 3-(naphthalen -1- ylmethyl )-1,2,4,5-tetraoxospiro [5.5 ] undecane was successfully obtained , but in very low yield (22% ), because of that the reaction conditions for this molecule needs to be optimized to obtain appropriate quantities for the biological tests.